Structural Performance and Stress Contour Analysis of Multi Utility Tunnels Using LISA V.8 Finite Element Analysis - Wahyudi Efendi, Aco (Journal of Research and Inovation in Civil Engineering as Applied Science (RIGID), 2024)
The growing complexity of urban infrastructure necessitates efficient management of utilities like electricity, water, and telecommunications. Multi Utility Tunnels (MUTs) provide a consolidated approach to housing these utilities, reducing surface disruption and enhancing maintenance efficiency. This study assesses the structural performance and stress distribution within MUTs using Finite Element Analysis (FEA) through LISA FEA V.8 software. The analysis involved detailed geometric modeling of the MUT, considering initial conditions and potential subsidence. Material properties for steel, concrete, wood, backfill soil, and the top surface layer were defined, focusing on their Young's modulus, density, and Poisson's ratio. The MUT was subjected to a uniform line pressure of 86.49 kN/m, representing vehicular traffic and pedestrian loads. Results showed that the applied stresses and observed deflections were within safe limits, with a tensile strength of 3.4 MPa and current stress at 3046 kN/m², indicating no risk of cracking. The observed deflection of 3.9 mm was significantly below the allowable limit of 10 mm, affirming structural stability. The reinforcing steel also exhibited stress levels well within its allowable limit, demonstrating the design's adequacy and ensuring the structure's safety and efficiency under the specified load conditions